Life table parameters of Neoseiulus californicus (Acari: Phytoseiidae), on the European red mite, Panonychus ulmi (Acari: Tetranychidae) in laboratory condition - Mostafa Maroufpoor; Youbert Ghoosta; Ali Asghar Pourmirza (Persian Journal of Acarology)
The life table parameters of Neoseiulus californicus (Athias-Henriot), a generalist predator of spider mites and small insects were investigated in laboratory condition at two constant temperatures: 20 and 25°C, 60 ± 5% relative humidity and a photoperiod of 16:8 h (L:D). The European red mite, Panonychus ulmi (Koch), an important pest of apple orchards in Iran, was used as prey (all stages). The duration of the immature stages ranged varied from 7.52 to 5.12 days, at 20 and 25°C, respectively. The net reproductive rate (R0) increased with increasing temperature from 20.84 female offspring to 31.46 female offspring at 20–25°C, respectively. The values of the intrinsic rate of increase (rm) and ﬁnite rate of increase (λ) were obtained to be highest at 25°C (0. 237 day –1 and 1.26 day–1, respectively), which was greater that those estimated at 20°C (0.161 day–1 and 1.17 day–1, respectively). The mean generation time (T) decreased with increasing temperature from 18.86 days to 14.45 days at 20–25°C, respectively. In conclusion, results showed that N. californicus would be able to develop at temperatures range of 20–25°C feeding on P. ulmi and has the suitable potential to control it.